A review of different sawing and drying techniques used in processing small-diameter logs. - Ratnasingam, Jegatheswaran; Abdullah, Aznor Marlina; Ramasamy, Geetha; Seng, Chee Yee (Asian Network for Scientific Information, 2013)
The importance of small diameter logs in the sawmilling sector in the South East Asian region cannot be underplayed, as plantation-grown fast growing tree species is the main source of wood raw material for the rapidly expanding wood products industry in the region. The aim of this study was therefore to highlight the different sawing and drying techniques used in the processing of small-diameter logs from the fast growing forest plantations. A significant difference in processing yields and also the costs of the different techniques are obvious and the industry is poised to take advantage of the benefits provided by the saw-dry-rip (SDR) method of processing small-diameter logs. As opposed to the conventional live-sawing method widely used in hardwood sawing in the South East Asian region, the saw-dry-rip (SDR) method offers a more viable option to process the small-diameter logs, with significant reductions in rejects, while improving the overall yield. The overall economic benefits gained through the adoption of this technique warrants serious consideration by the sawmilling sector throughout the region.